2022
DOI: 10.1186/s40249-022-01002-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and virological surveillance of influenza viruses in China during 2020–2021

Abstract: Background During the coronavirus disease 2019 (COVID-19) pandemic, seasonal influenza activity declined globally and remained below previous seasonal levels, but intensified in China since 2021. Preventive measures to COVID-19 accompanied by different epidemic characteristics of influenza in different regions of the world. To better respond to influenza outbreaks under the COVID-19 pandemic, we analyzed the epidemiology, antigenic and genetic characteristics, and antiviral susceptibility of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
(21 reference statements)
4
18
0
Order By: Relevance
“…Another interesting finding was that the diversity of influenza 45 The disappearance of influenza B/ Yamagata viruses during the COVID-19 period was also observed, which is consistent with the research of Koutsakos et al 46 and Paget et al, 47 suggesting that influenza B/Yamagata should be closely monitored globally. The influenza outbreaks were mainly influenza A/ H1N1 and A/H3N2 viruses in 2018 and 2019, characterized by high transmission ability, high infection rate, and rapid antigen variation, 48,49 which was similar to results in previous studies on pandemic influenza.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another interesting finding was that the diversity of influenza 45 The disappearance of influenza B/ Yamagata viruses during the COVID-19 period was also observed, which is consistent with the research of Koutsakos et al 46 and Paget et al, 47 suggesting that influenza B/Yamagata should be closely monitored globally. The influenza outbreaks were mainly influenza A/ H1N1 and A/H3N2 viruses in 2018 and 2019, characterized by high transmission ability, high infection rate, and rapid antigen variation, 48,49 which was similar to results in previous studies on pandemic influenza.…”
Section: Discussionsupporting
confidence: 85%
“…Before 2020, the influenza A/H1N1 subtypes dominated over other subtypes/lineages. However, influenza B showed an upward trend during the COVID‐19 period, with only B/Victoria lineage been isolated from March 2021 to December 2021, which was consistent with the national surveillance of influenza during 2020–2021 45 . The disappearance of influenza B/Yamagata viruses during the COVID‐19 period was also observed, which is consistent with the research of Koutsakos et al 46 and Paget et al, 47 suggesting that influenza B/Yamagata should be closely monitored globally.…”
Section: Discussionsupporting
confidence: 84%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of IBV activity observed in our study was consistent with other places in China. 13,16,17 Beijing upgraded the NPIs like school and workplace closing, cancel public events, as well as restrictions on gatherings during 2021/2022 winter season to prevent the outbreak and spread of Omicron. Based on NPIs data set and generalized additive models, Zhang et al 5 reported that "cancelling public events" and "restrictions on internal travel" measures played an important role in the reduction of influenzalike illness.…”
Section: Discussionmentioning
confidence: 99%